The aesthetic properties of the genre of classical Chinese poetry Ci and the spiritual-moral basis of their formation (from the point of view of “The beauty of weakness as a virtue”) - Ye, Fangfang (Жанры речи)
The article analyzes the aesthetic properties of the genre of classical Chinese poetry Сi and the spiritual-moral basis of their formation from the point of view of the concept “The beauty of weakness as virtue”, put forward by the famous specialist in the field of classical Chinese poetry Ye Jiaying. The relevance of the topic is determined by the fact that, although many classical Chinese Ci poems have been translated into Russian, there is little research on the aesthetic properties of the genre itself, especially from the point of view of modern Chinese poetic theory. The article uses methods of description, interpretation, historical-cultural and contextual analysis. The article aims is to explain the aesthetic properties and the reason for their formation from the point of view of the concept “The beauty of weakness as a virtue”. It is ahown that the aesthetic properties of the Ci lie in the presence of a deeply hidden, inexhaustible understatement in poetry. Formally, this is created by alternating long and short verses; at the semantic level, the understatement in poetry appeared as a result of the forced transformation of the inexpressible feelings and emotions of the poet, who was in a weak position, but at the same time showed the quality of endurance, restraint and commitment to something good. The influence of the ideas of Confucianism on the formation of the aesthetic properties of Ci poetry allows us to speak not only about its artistic-aesthetic, but also its spiritual-moral significance. Altogether, it allows us to give a decent assessment of the Ci genre, which for a long time was perceived as a genre less valuable than the Shi genre.